Investigation Of Sporting Habits and the Attitudes Related to Physical Education during the COVID-19 Pandemic - Gábor, Fintor (Central European Journal of Educational Research, 2022)
Several domestic and international studies confirm the benefits of regular sports activities regarding healthy attitudes (Földesiné, 2008; Shephard et al., 2013). On the one hand, our research aimed to survey sporting habits (with a special focus on the impacts of the Coronavirus epidemic on physical activities). On the other hand, we investigated the participants’ attitudes regarding daily physical education classes. In the course of our research, we conducted a representative data recording among Hungarian citizens 18 years old or above (n = 1015) regarding gender, age, education level, and type of habitation. The vast majority (71%) of the surveyed population is not involved in any kind of sports activities (which corresponds with the outcomes of previous investigations), however, in this aspect, the impacts of COVID-19 are marginal. Sports activities are most typical to males with a higher level of education, who reside in larger cities. The most popular sports activities are running/jogging (36.3%), cycling (16.6%), and soccer (16.2%). The opinions regarding daily physical education classes are rather positive: the majority consider the increased number of PE classes a useful development. These opinions are held mainly by those who either are active in sports or who live in Budapest. A quintessential part of life in the COVID-19 pandemic, healthier lifestyles could certainly benefit from quality physical and sports education. If this quality is further improved, it may also dispel some of the negative ideas about sporting habits.